Optimisation of Operational Management Through the Use of Information Technology to Improve Service Quality at the Expedition Services of Railway Logistics (KALOG) Madiun Representative - Iqbal Aristotle Khatistyarso; Daman Sudarman (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
The purpose of the study was to determine how the application of information technology to improve operational efficiency and service quality at the expedition service of Railway Logistics (KALOG) Madiun representative. This research uses a qualitative approach with a case study at KALOG Madiun, focusing on the application of the KAI Logistics TRAX application to optimize operational management and improve service quality. Data were collected through in-depth interviews, participatory observation, and documentation studies. Data analysis was carried out by transcription, narration of findings, triangulation, and drawing conclusions and recommendations for operational improvement. Based on the results of the study, the use of the KAI Logistics TRAX application has facilitated KALOG's operations, especially in real-time tracking of goods, digital ordering, and tariff checking. However, the adoption rate of this application at KALOG Madiun is still low, due to the lack of promotion, customer preference for manual methods, and limited digital infrastructure. This low adoption hampers operational efficiency, increases costs, and reduces the quality of service to customers.